1996
DOI: 10.1093/nar/24.22.4535
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Methods of DNA and RNA Fluorescent Labeling

Abstract: Several procedures have been described for fluorescent labeling of DNA and RNA. They are based on the introduction of aldehyde groups by partial depurination of DNA or oxidation of the 3'-terminal ribonucleoside in RNA by sodium periodate. Fluorescent labels with an attached hydrazine group are efficiently coupled with the aldehyde groups and the hydrazone bonds are stabilized by reduction with sodium cyanoborohydride. Alternatively, DNA can be quantitatively split at the depurinated sites with ethylenediamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 36 publications
0
112
0
1
Order By: Relevance
“…1), RNA 59-adenylation using T4 DNA ligase and a-32 P-ATP is an alternative approach to RNA 59-radiolabeling that may be of practical utility. Finally, because the adenylate moiety has an ribose 29,39-diol group that may be oxidized with sodium periodate to aldehydes, RNA 59-adenylation enables labeling of the 59-terminus by subsequent reductive amination or other coupling reactions using a variety of amine reagents combined with biophysical probes (Wells and Cantor 1977;Odom et al 1980;Proudnikov and Mirzabekov 1996). This overall 59-labeling approach will be particularly useful when a method for RNA labeling is sought that does not require incorporation by solid-phase synthesis of special 59-terminal RNA nucleotides and the RNA 39-terminus cannot be used as a modification site, e.g., when it is blocked as a 29,39-cyclic phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…1), RNA 59-adenylation using T4 DNA ligase and a-32 P-ATP is an alternative approach to RNA 59-radiolabeling that may be of practical utility. Finally, because the adenylate moiety has an ribose 29,39-diol group that may be oxidized with sodium periodate to aldehydes, RNA 59-adenylation enables labeling of the 59-terminus by subsequent reductive amination or other coupling reactions using a variety of amine reagents combined with biophysical probes (Wells and Cantor 1977;Odom et al 1980;Proudnikov and Mirzabekov 1996). This overall 59-labeling approach will be particularly useful when a method for RNA labeling is sought that does not require incorporation by solid-phase synthesis of special 59-terminal RNA nucleotides and the RNA 39-terminus cannot be used as a modification site, e.g., when it is blocked as a 29,39-cyclic phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been suggested to alleviate this problem, such as the use of helper oligonucleotides [130] and a two-probe proximal chaperon detection system [158] to mitigate the effects of target secondary structure hindrances, an appropriate labeling method [63], and a protocol to achieve optimized target lengths [126,164,197]. Since long targets can form secondary and tertiary structures that hinder efficient probe-target duplex formation, the sizes of the target molecule and its amplicon are often reduced via chemical, enzymatic or thermal fragmentation methods [24,87,104,126,138,158]. Liu et al have recently elegantly reviewed these issues and experimentally demonstrated that microarray hybridizations with short rRNA fragments were more dependent on target sequence than on the competition between probe-target interaction and RNA self-folding [103].…”
Section: Hybridization and Wash Conditionsmentioning
confidence: 99%
“…Various enzyme-assisted hybridization strategies (also used in SNP and resequencing assays [52,98]) are being applied because of their promise in strongly discriminating single mismatches located near the 3 0 -end of microarray probes [34,75,101,119,135,138,145].…”
Section: Further Developments and New Perspectives Regarding Array Sementioning
confidence: 99%
“…Cyclic phosphate termini are also readily removed after the reaction if a free 2¢,3¢-diol is desired (Schürer et al 2002). As an alternative to capping with a 2¢,3¢-cyclic phosphate, the 3¢-terminal ribose moiety of the substrate could be oxidized with sodium periodate (Proudnikov and Mirzabekov 1996). Such periodate oxidation would be an acceptable capping approach if the resulting 3¢-terminal aldehyde functional groups do not interfere with subsequent applications of the RNA.…”
Section: Wwwrnajournalorg 317mentioning
confidence: 99%